An Examination and Extension of the Theory of Gamified Learning: The Moderating Role of Goal Orientation. (August 2021) - Garcia- Marquez, Caribay; Bauer, Kristina N.
Background: Landers (2014) proposed the theory ofgamified learning to provide a theoretical framework forgamification research. Unfortunately, little empirical work has tested this theory. Thus, the current study aimed to close this gap by examining the theory's mediational pathway as well as exploring the moderating role ofgoal orientation on the pathway from Assessment game attributes (i.e., assessment and progress) toself-efficacy to learning outcomes. Method: A gamified resume course was developed on agamification software platform. Participants ( N = 185) were recruited through Amazon Mechanical Turk and randomly assigned to one of four conditions (i.e., badges, progress bar, badges and progress bar, and control). Participants responded to a pre-course questionnaire containing demographics and thegoal orientation measure, were directed to the course website to complete the gamified resume course and knowledge measure, and were finally re-directed to a post-course questionnaire collecting job search self-efficacy. Results: There was little support for the hypothesized moderated mediation model. However, an interesting outcome of this study was the significant conditional indirect effect of the badge condition for average learning and high avoid performance goal orientations, suggestingbadges can improveself-efficacy ingamified learning . Discussion and Conclusion: A key takeaway of this study was preliminary evidence suggestingbadges may help mitigate the negative effects of avoid performancegoal orientation onself-efficacy . This finding demonstrates how individual differences play a role in learners' responses to game attributes in agamified learning experience. Practical implications, limitations, and directions for future research are discussed.